2009
DOI: 10.1111/j.1360-0443.2009.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending drug ethno‐epidemiology using agent‐based modelling

Abstract: Agent-based modelling was used to integrate ethno-epidemiological data on psychostimulant use, and to test the probable impact of a specific intervention on the prevalence of drug-related harms. It also established a framework for collaboration between research disciplines that emphasizes the synthesis of diverse data types in order to generate new knowledge relevant to the reduction of drug-related harms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…A linkage with the province-wide ART dispensary provides a complete retrospective and prospective profile of exposure to treatment and adherence. Consistent with ethno-epidemiological methods [39, 40], we deployed qualitative methods alongside this epidemiological research program to explore individual, social, and structural influences on ART interruptions in a setting implementing TasP, and thus inform the refinement of this structural intervention. This study was approved by the Providence Healthcare/University of British Columbia Research Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
“…A linkage with the province-wide ART dispensary provides a complete retrospective and prospective profile of exposure to treatment and adherence. Consistent with ethno-epidemiological methods [39, 40], we deployed qualitative methods alongside this epidemiological research program to explore individual, social, and structural influences on ART interruptions in a setting implementing TasP, and thus inform the refinement of this structural intervention. This study was approved by the Providence Healthcare/University of British Columbia Research Ethics Board.…”
Section: Methodsmentioning
confidence: 99%
“…Research in the area of network and cluster analysis has revealed variance in the drug using subtypes [24]. Other research has used ethnographic methods to establish what are the different stages of psycho-stimulant use [21]. In communities centred on the consumption of illicit drugs, high and low-risk behavioral drug consumption patterns can be spread because of tight social connections within these communities.…”
Section: Peer Association and Drug Usage Patternsmentioning
confidence: 99%
“…There is increasing acceptance of post-positivism in quantitative research, as well as recognition of straight-forward realism in much applied qualitative research, and a growing respect for the need to reflect on how research questions and methods relate to epistemological assumptions. Collaborations between ethnography, epidemiology and mathematical modelling provide examples (Agar, 2003; Bourgois et al, 2006; Ciccarone & Bourgois, 2003; Moore et al, 2009). …”
Section: The Marginality Of Qualitative Research In Addiction Journalsmentioning
confidence: 99%